Validating a composite endpoint for acceptability evaluation of oral drug formulations in the pediatric population: a randomized, open-label, single dose, cross-over study - Münch, Juliane; Schwarzwälder, Anna Lena; Kloft, Carolin; Bosse, Hans Martin; Wargenau, Manfred; Reidemeister, Sibylle; Klingmann, Ingrid; Klingmann, Viviane (Frontiers in Pharmacology, 2024)
Objective This study aimed to validate the newly developed composite acceptability endpoint to investigate acceptability of oral pediatric drug formulations that integrates swallowability and palatability assessments. Methods In this open-label study acceptability of oral formulations was tested in three age groups (1–<6 months, 6–<12 years, and 12–<18 years) with a 2-way cross-over design in children aged 1–<6 months (syrup and mini-tablets), and with an incomplete block design of four sequences with three out of four formulations (syrup, mini-tablets, oblong tablet, and round tablet) each in children aged 6–<18 years. The primary endpoint was acceptability derived from the composite acceptability endpoint. Secondary endpoints were palatability and acceptability derived from swallowability. Results A total of 320 children were stratified into three age groups (80 children aged 1–<6 months, 120 children aged 6–<12 years, and 120 children aged 12–<18 years). All participants completed the study. Age-specific differences were observed in acceptability derived from the composite acceptability endpoint. Mini-tablets had the highest acceptability in participants aged 1–<6 months and 6–<12 years while the oblong tablet was leading in adolescent participants (12–<18 years). Conclusion This study demonstrated that the composite acceptability endpoint method integrating both swallowability and palatability assessments is a sensitive method to assess acceptability of drug formulations in children of different age. Clinical Trial Registration https://drks.de/search/de, identifier DRKS00027948.